INNOVATIVE CONCEPTS IN HOTEL BUSINESS: INTERNATIONAL AND RUSSIAN EXPERIENCE - K. I. Shchetinina (Vestnik MGIMO-Universiteta)
According to the experts of PricewaterhouseCoopers Company, hotel segment in Russia in 2013 year is about to develop and increase sales, despite crisis preconditions and an ambiguous economic situation in the world. The innovative hotel concept is one of the most popular subjects among hotel real es-tate developers and hotel operators. Indeed the innovative hotel concept is an additional way of promoting hotel services. Leading international and Russian engineers acquire experience in creating a unique hotel concept: both in premium and economy class. The article describes such forms of innovative hotel concepts as business and design hotels, capsule hotels, budget hotels, «Women only» hotels. The author of the article studies key aspects of the international approach «the blue way» to the hotel industry. If the building is environment-oriented and fulfills all the requirements for economy and functionality, it represents an example of this complete and balanced approach.